Comparative analysis of stress markers, metabolic health, and gut microbiota in healthy and disabled dogs in long-term shelters in Thailand - Adul Saengthong; Janine L. Brown; Patcharapa Towiboon; Khanittha Punturee; Songphon Buddhasiri; Korakot Nganvongpanit; Veerasak Punyapornwithaya; Wuithipong Tocharoennirattisai; Jaruwan Khonmee (PLoS ONE, 2026)
Regular welfare assessments are essential for identifying and addressing the physical, behavioral, and emotional needs of shelter dogs, thereby ensuring their well-being and improving chances for adoption or long-term stability within the shelter environment. This study compared biomarkers of physiological stress [fecal glucocorticoid metabolites (fGCM)], metabolic status [serum malondialdehyde (MDA), glucose, triglycerides, low- (LDL) and high- (HDL) density lipoproteins], and fecal microbiota composition over a 1-month period in healthy and spinal-injured disabled dogs housed in a large dog rescue shelter in Thailand for over 1 year. No significant differences in fGCM concentrations were observed between groups, indicating comparable levels of physiological stress in healthy and disabled dogs under long-term shelter conditions. In contrast, disabled dogs exhibited significant metabolic and oxidative alterations, including elevated MDA and glucose, along with lower triglyceride and HDL concentrations. Microbial analyses revealed comparable alpha diversity but differences in beta diversity between groups. Notably, disabled dogs exhibited a reduced Firmicutes-to-Bacteroidetes (F/B) ratio and decreased relative abundances of beneficial taxa such as Peptostreptococcaceae . These findings suggest that, despite comparable hormonal stress indicators, disabled dogs may experience subclinical physiological shifts that warrant more nuanced welfare monitoring. A multifactorial assessment incorporating metabolic and microbial parameters is recommended to ensure comprehensive welfare evaluation for physically impaired shelter dogs.